Heat Treatment as a Safe-Handling Procedure for Rift Valley Fever Virus - Maria Anele Romeo; Eliana Specchiarello; Cosmina Mija; Verdiana Zulian; Massimo Francalancia; Fabrizio Maggi; Anna Rosa Garbuglia; Daniele Lapa (Pathogens)
Rift Valley Fever virus (RVFV) is a mosquito-borne virus with high pathogenic potential in ruminants and humans. Due to its high potential for spreading, it is considered a priority pathogen, and it is included in the Bluepoint list of the World Health Organization (WHO). Given the high pathogenic potential of the virus, it is crucial to develop a rapid heat-mediated inactivation protocol to create a safer working environment, particularly in medical facilities that lack a biosafety level 3 laboratory required for direct handling of RVFV. Our results reveal the broad tissue tropism of RVFV, showing the virus’s capacity for replication in various cell lines. In terms of the thermal stability of RVFV, our findings showed that a 70 °C heat treatment did not fully inactivate the virus within 15 min. However, when exposed to 80 °C and 95 °C, the virus was completely inactivated after 15 min and 5 min, respectively. Additionally, our results indicated that heat-treatment only slightly decreased the integrity of the RVFV genome whether there is a high or low number of viral RNA copies. Overall, the study established a straightforward protocol for heat inactivation that may be beneficial in handling clinical and research samples of RVFV.